Isolation and Characterization of polyphenolic compounds from Ethanolic Extract of Hibiscus syriacus - Pradeep Singh Tomar,; Dr Gajanand Engla, (The Bioscan, 2025)
Background:Polyphenolic compounds are known for their structural diversity and potential therapeutic applications. Hibiscus syriacus, a plant traditionally used in herbal medicine, contains a rich profile of phytoconstituents, including polyphenols. This study aimed to isolate and structurally characterize polyphenolic compounds from the ethanolic extract of H. syriacus flowers using advanced spectroscopic techniques. Methods: Flowers of H. syriacus were collected, shade-dried, powdered, and extracted using Soxhlet extraction with ethanol. The crude extract was partitioned and subjected to column chromatography and Sephadex LH-20 for fractionation. Final purification was achieved using reversed-phase semi- preparative high-performance liquid chromatography (HPLC). Isolated compounds were characterized by Fourier Transform Infrared Spectroscopy (FTIR), Proton and Carbon Nuclear Magnetic Resonance (¹H and ¹³C NMR), and Mass Spectrometry (MS) for detailed structural elucidation. Results: Two distinct polyphenolic compounds (Compound 1 and Compound 2) were successfully isolated and identified. FTIR analysis confirmed the presence of key functional groups such as hydroxyl, aromatic rings, and carbonyl groups. NMR spectra provided detailed insights into the structural framework, revealing substitution patterns consistent with known polyphenolic structures. Mass spectrometry determined the molecular weights of Compound 1 (MW 164.16; m/z 165.05) and Compound 2 (MW 194.18; m/z 195.06), confirming their purity and identity. Conclusion:The study successfully demonstrated the extraction, isolation, and spectroscopic characterization of two polyphenolic compounds from Hibiscus syriacus flowers. These findings contribute to the phytochemical profiling of the species and provide a foundation for future research into their potential biological or pharmaceutical applications.